Multiple phases of yttrium-doped molybdenum trioxide nanorods as efficient dye degrader and bactericidal agents with molecular docking analysis - Ikram, Muhammad; Shujah, Tahira; Shahzadi, Anum; Haider, Ali; Rafique, Aqsa; Ul-Hamid, Anwar; Nabgan, Walid; Haider, Syed Karrar; Alshahrani, Thamraa; Algaradah, Mohammed M.; Yousaf, S. Amber; Haider, Junaid (Chemosphere (Oxford), 2023)
Contaminants removal is usually becoming an exciting subject of research from water considering their environmental and ecological effects. This work provides pathways to remove organic pollutants from water via nanomaterials and is used as an antibiotic against bacteria like Escherichia coli (E. coli). In this study, molybdenum trioxide (MoO3) and yttrium (Y) doped (2 and 4%) MoO3 nanorods were synthesized by co-precipitation method. Advanced characterization techniques have been introduced to study textural structures, morphological developments, and optical characteristics of produced products. X-ray diffraction studied multiple crystalline structures of prepared samples as hexagonal, orthorhombic, and monoclinic of pure MoO3 with decrease in crystallinity and crystallite size upon Y doping. UV–visible spectroscopy unveiled a redshift (bathochromic effect) in absorption pattern attributed to band gap energy (Eg) decreases. Photoluminescence spectra examined the recombination rate of electrons (e−) and holes (h+) as charge carriers. A sufficient catalytic activity (CA) was observed against methylene blue (MB) dye in an acidic medium (99.74%) and efficient bactericidal action was studied against (E. coli) with zone of inhibition (5.20 mm) for 4% Y-doped MoO3. In addition, in silico docking demonstrated potential inhibitory effect of produced nanomaterials on FabH and FabI enzymes of fatty acid biosynthesis. [Display omitted] •The removal of organic pollutants from water using nanomaterials was studied.•MoO3 and Y doped MoO3 nanorods were prepared by co-precipitation technique.•Significant catalytic activity was observed for 4% Y-doped MoO3•Y-doped MoO3 nanorods as possible inhibitors of FabH and FabI enzymes